2022
DOI: 10.1038/s41598-022-07142-2
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between antibiotic consumption and the occurrence of multidrug-resistant organisms in a Malaysian tertiary hospital: a 3-year observational study

Abstract: Inappropriate use of antibiotics has been shown to contribute to the occurrence of multidrug-resistant organisms (MROs). A surveillance study was performed in the largest tertiary care hospital in Kuala Lumpur, Malaysia, from 2018 to 2020 to observe the trends of broad-spectrum antibiotics (beta-lactam/beta-lactamases inhibitors (BL/BLI), extended-spectrum cephalosporins (ESC), and fluoroquinolones (FQ)) and antibiotics against MRO (carbapenems, polymyxins, and glycopeptides) usage and the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Indeed, there is an alarmingly increasing antimicrobial resistance noted in Greek hospitals and the community, while, on the other hand, the high prevalence of antimicrobial resistance noted can probably be correlated with the high consumption of antimicrobials. There are several studies directly linking the use of antimicrobials with the development of antimicrobial resistance [ 25 , 26 , 27 , 28 , 29 ]. More than 50% of patients in this survey were receiving antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is an alarmingly increasing antimicrobial resistance noted in Greek hospitals and the community, while, on the other hand, the high prevalence of antimicrobial resistance noted can probably be correlated with the high consumption of antimicrobials. There are several studies directly linking the use of antimicrobials with the development of antimicrobial resistance [ 25 , 26 , 27 , 28 , 29 ]. More than 50% of patients in this survey were receiving antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…The use of antibiotics changes the intestinal microbiota and compromises the immunity of patients with COVID-19 [ 6 ]. In addition, long-term use of antibiotics causes resistance of existing bacteria and old strains that are resistant to most antibiotics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar proportion in either ICU indicated that clinicians were practicing high rates of empirical carbapenems, despite the negative culture or growth of the organism(s) susceptible to narrower spectrum beta-lactam antibiotics or alternatives. Although carbapenems were the recommended empirical choice for ICU patients with severe sepsis [ 13 ], only a small percentage of prescriptions had positive growth of ESBL-producing Enterobacterales , which were predominantly Klebsiella spp., similar to another tertiary hospital in the same region in Malaysia [ 18 ].…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the same proportion at 70% was found during the pandemic period [ 5 ]. However, the issue of increased antibiotic consumption during the pandemic period is mostly reflected in the proportion of patients being prescribed antibiotics [ 2 , 5 ], where few reported the magnitude of antibiotic utilization in ICU with the measure of DDD [ 3 ], which is also an important indicator for usage trend monitoring, the impact of intervention, global comparison [ 16 ], as well as correlation with resistance trends [ 12 , 17 , 18 ]. The decrease in total ICU admissions was attributed to the opening of the COVID-19 ICU with redistribution of manpower and the closure of the operating theatre elective list during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%